Stress at work: individuals or structures? - Davies, A (Oxford University Press, 2021)
Stress is a significant practical problem in modern workplaces. According to the Health and Safety Executive (HSE), more than half of all working days lost to ill health each year are attributed to stress, depression or anxiety. This article offers an overview of the occupational psychology literature on workplace stress, focusing on the job demands–resources or JD-R model, developed by Demerouti et al., and highlighting two important points: first, that stress at work is not just about excessive job ‘demands’ but also about inadequate ‘resources’ to cope with those demands; second, that stress-related ill-health is not just a matter of vulnerability on the part of the individual worker, but is also about the way in which the workplace is organised. The article then draws on these insights to offer a critique of the way in which health and safety law and tort law approach workplace stress, arguing that both bodies of law are overly focused on treating stress as a matter of individual vulnerability. It concludes by drawing out some broader implications of the occupational psychology literature for areas of employment law less obviously related to workplace stress, and for casual or platform working.